A cold treachery ebook - Todd, Charles (Inspector Ian Rutledge Mystery, 2005)
“Stunning . . . the tragic sweep of Todd’s historical mysteries grows more expansive with each novel.”— The New York Times Book Review Called out into the teeth of a violent blizzard, Inspector Ian Rutledge faces one of the most savage murders he’s ever encountered. He might have expected such unspeakable carnage on the World War I battlefields where he’d lost much of his soul—and his sanity—but not in an otherwise peaceful farm kitchen in remote Urskdale. Someone has murdered the Elcott family without the least sign of struggle. But when the victims are tallied, the local police are in for another shock: One child is missing. Now the Inspector must race to save a young boy before he’s silenced by the merciless elements—or the even colder hands of the killer who hides in the blinding snow. Praise for A Cold Treachery “Todd’s Ian Rutledge mysteries are among the most intelligent and affecting being written these days.” — Washington Post Book World “Brilliant.” — Chicago Tribune “Traditional mystery lovers who prefer their whodunits enriched with psychological insight will heartily embrace A Cold Treachery . . . . A superb effort.” — Publishers Weekly (starred review) “Brilliantly conceived and elegantly executed.” — Strand magazine